Plasticidade Ecológica e Comportamental em Ambiente Hostil: O Manguezal como Último Refúgio de Cebus xanthosternos Wied-Neuwied 1820 - Mendes, Raone Beltrão (2015)
The yellow-breasted capuchin, Cebus xanthosternos, is listed as critically endangered by the IUCN, due primarily to the loss of habitat and reduction of populations. The behavioral abilities of these monkeys, which are typical of the capuchins (lato sensu), allow them to occupy an ample diversity of the habitats found within the geographic range of the species, including mangrove. Despite being highly productive, the mangroves are characterized by a low diversity of plant species, in particular those that produce edible fruit, the primary component of the capuchin diet. Mangroves are also threatened by the expansion of urban development and changes in soil use. Despite this, C. xanthosternos can be found in mangroves throughout its coastal distribution. Considering this, the present study had three objectives: (i) to determine the factors that lead C. xanthosternos to occupy mangroves, (ii) identify the key features of the ecology of the species that allow it to survive in this ecosystem, and (iii) understand the population dynamics of the species in the mangrove, in order to establish effective conservation strategies that favor both the maintenance of the mangroves and the survival of their resident populations of C. xanthosternos. The occurrence of C. xanthosternos populations within the coastal distribution of the species was confirmed through interviews (non-directed and snowball approaches) with the residents of local communities adjacent to mangroves. To identify the ecology characteristics of the species fundamental to its survival in the mangrove, the population of Cabeço Island, at the mouth of the São Francisco River in Brejo Grande, Sergipe (Brazil) was monitored using camera traps (Acorn, LTL-5210A) for the evaluation of habitat use and behavioral patterns. Fecal samples were also collected in litter traps for subsequent analysis. A captive group of C. xanthosternos was observed on an island enclosure in Salvador Zoo, with the aim of providing complementary data on the behavior of the species in the context of a semi-aquatic habitat. To evaluate population dynamics and contribute to the development of XXI conservation measures, a historical series of the satellite images available for the mouth of the São Francisco was reviewed for the understanding of the morphodynamics of the local mangrove. These data were analyzed together with information provided by local residents on the occurrence of capuchins in the area and shifts in the configuration of local populations. A total of 61 localities were visited during the surveys, and the presence of C. xanthosternos in the local mangrove was recorded at eight of these sites. In three cases, the occurrence of capuchins in the mangrove was occasional, and related primarily to visits to the neighboring areas of salt marsh, whereas at five sites, capuchin populations inhabited the mangrove on a permanent basis. The existence of permanent populations was related to the size of the tract of mangrove and the loss of neighboring terra firme forests, in addition to the expansion of urban and agricultural development. Habitat use at Cabeço Island appeared to be seasonal, with differences in visitation rates on the average of number of individuals and total duration, recorded at the sampling stations P02, P04, P05 and P06, between the rainy and dry seasons, although without significant differences. The behavior of C. xanthosternos related to its survival in mangrove habitats included (a) use of tools such as sticks and manual fishing for items in the water (captive observations), (b) use of proto-tools for the processing of specific resources, such as crabs (Ucides cordatus, Goniopsis cruentata, Aratus pisonii), (c) exploitation of crops (coconut, Cocos nucifera; beans, Phaseolus sp.; cassava, Manihot sp.; maize, Zea mays; watermelon, Citrullus sp.; and oil palm, Elaeis guineensis) in neighboring plantations, (d) raiding of fish and crustacean traps. The configuration of the mangroves at the mouth of the São Francisco River has changed gradually, but constantly, over time, resulting in modifications of the distribution of creeks and mangrove habitats, and the progressive isolation and grouping of the different tracts of mangrove. This scenario has and has had a direct effect on past and present migrations of individuals among the three distinct present-day populations of C. xanthosternos found in the mangrove complex of São Francisco River mouth. Conservation measures needed for the species in this ecosystem include the regulation of soil use, to minimize habitat loss, as well as the establishment of dispersal routes between fragments to ensure gene flow between isolated populations. Management programs should also be established, even on a long-cycle time scale, in order to guarantee the XXII renovation of genetic variability in isolated populations and minimize the effects of stochastic processes.